Does Exposure to Type 1 Diabetes In Utero Increase the Risk of Metabolic Syndrome, Especially Abdominal Obesity, in Young Adults?. (29th May 2020) - Summer, Suzanne; Khoury, Jane; Bowers, Katherine; Lima, Taylor; Hunt, Jennifer; Ollberding, Nicholas
Abstract: Objectives: Metabolic syndrome (MetS) is a clustering of metabolic abnormalities including abdominal obesity that can lead to cardiovascular disease, diabetes, and stroke. Exposure to maternal diabetes in utero increases MetS risk in offspring. Consuming a healthy diet may reduce the risk. The MetS severity z-score (MetS-z) is a sex- and race-specific score developed by Gurka et al. to indicate MetS risk or severity on a continuous scale. We sought to examine if offspring of mothers with Type 1 Diabetes (T1D) have greater risk or severity of MetS, particularly with respect to abdominal obesity, compared to subjects from the National Health and Nutrition Examination Survey (NHANES). Methods: The Transgenerational Effects of Adult Morbidity (TEAM) study is a prospective cohort study investigating the impact of gestational exposure to maternal T1D on metabolic health of offspring. To date, 100 young adult (24–42 y) offspring of mothers with T1D have been enrolled. TEAM participants were compared to a population sample of ∼1:2 age-, sex- and race-matched controls from NHANES 2015–2016. Abdominal obesity was assessed by sagittal abdominal diameter (SAD), an indicator of abdominal visceral fat. Usual diet was estimated by averaging intake from multiple 24-hour diet recall interviews. MetS-z was calculated with equations specific for sex, age, and race, and diet quality was assessed by the Healthy Eating Index (HEI)-2015 score. Descriptive and regression analyses were employed to compare TEAM and NHANES participants on MetS-z and SAD. HEI score was examined as a covariate and a potential moderator. Results: SAD was higher in TEAM than NHANES participants (23.4 vs 21.8 cm, P  = 0.005). No material differences in MetS-z (–0.02 vs −0.17, P  = 0.18) or HEI score (51.3 vs 48.9, P  = 0.26) were observed. SAD and MetS-z were highly correlated (r = 0.72, P  < 0.001). HEI score exhibited a weak inverse correlation with both SAD and MetS-z (r = −0.19 and r = −0.17). HEI was not found to modify the association between cohort membership and MetS-z or SAD. Conclusions: We observed higher SAD in offspring of mothers with T1D compared to NHANES participants and this effect persisted after controlling for HEI. SAD is associated with increased risk for MetS, yet no material difference in MetS z-score was observed between the groups. Funding Sources: NIH, NIDDK R01DK109956; 5UL1TR001425–04.